2021
DOI: 10.1021/acs.jpcc.0c10525
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Charge Density Modulations in Photoexcited CuWO4

Abstract: Copper tungstate (CuWO 4 ) is an important semiconductor with a sophisticated and debatable electronic structure that has a direct impact on its chemistry. Using the PAL-XFEL source, we study the electronic dynamics of photoexcited CuWO 4 . The Cu L 3 X-ray absorption spectrum shifts to lower energy upon photoexcitation, which implies that the photoexcitation process from the oxygen valence band to the tungsten conduction band effectively inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…To do so, we tested the CuWO 4 :580 electrode with an electrolyte containing H 2 O 2 as an electron donor. Hydrogen peroxide is much more easily oxidizable than water (+0.68 V SHE vs 1.23 V SHE for water) and has a higher reaction rate (H 2 O 2 to H 2 O is a 2-hole process, while H 2 O to O 2 is a 4-hole process) . The current doubled to 0.67 mA cm –2 at 1.23 V SHE in the presence of H 2 O 2 (Figure C).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To do so, we tested the CuWO 4 :580 electrode with an electrolyte containing H 2 O 2 as an electron donor. Hydrogen peroxide is much more easily oxidizable than water (+0.68 V SHE vs 1.23 V SHE for water) and has a higher reaction rate (H 2 O 2 to H 2 O is a 2-hole process, while H 2 O to O 2 is a 4-hole process) . The current doubled to 0.67 mA cm –2 at 1.23 V SHE in the presence of H 2 O 2 (Figure C).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, the CuWO 4 band gap can be narrowed by substituting tungsten with molybdenum in quaternary CuW x Mo y O 4 . For example, CuW 0.5 Mo 0.5 O 4 has a band gap of 2.0 eV, corresponding to an absorption edge of 650 nm. This tungstate family is stable in neutral and slightly basic pH because of the overlap between Cu 3d orbitals with O 2p orbitals. , This hybridization is also responsible for the negative shift of the CuWO 4 valence band compared to that of binary WO 3 . Moreover, CuWO 4 is suitable to assemble heterojunction systems with BiVO 4 , , likewise WO 3 . …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in CuWO 4 , it has been reported that unoccupied Cu 3d orbitals act as a spectator state during photoexcitation. 48 If the excited electron occupies primarily the Cu 4s orbital, the charge density around the Cu atoms increases; however, the newly formed Cu 1+ would remain as a 3d 9 system. Because the d orbital occupancy remains largely unchanged, we expect no significant change in multiple structures in the XANES spectrum.…”
mentioning
confidence: 99%
“…There is precedence for photoexcitation into Cu 4s conduction band states. For example, in CuWO 4 , it has been reported that unoccupied Cu 3d orbitals act as a spectator state during photoexcitation . If the excited electron occupies primarily the Cu 4s orbital, the charge density around the Cu atoms increases; however, the newly formed Cu 1+ would remain as a 3d 9 system.…”
mentioning
confidence: 99%